Investigation of factors influencing tone reproduction in screen printing - Szentgyörgyvölgyi, Rozália; Borbély, Ákos; Novotny, Erzsébet (University of Pardubice, 2011)
Screen printing is one of the oldest printing processes. While its theory and tools did not change significantly, the technology underwent a considerable improvement during its history, and continues to develop in the 21st century as well. Screen printing allows deposition of a thick layer of ink onto the substrate, enabling the use of ideally any kind of substrate. In the case of this technology it is increasingly important to choose the right screen ruling according to the estimated viewing distance. Despite the significant technological development, halftone screen printing remains a challenge. Factors influencing quality are in close interaction with each other. For the optimal output it is necessary to control these factors more or less independently to produce high density screen prints in high quality. Tone values of the screen print are primarily influenced by the density of the mesh and thread weight. In practice the smallest dot will determine the usable highest screen ruling. In our research we investigated the effect of screen ruling on print quality. Test charts were printed on PVC and PP substrates using 36 l cm–1 and 60 l cm–1 screens ruling. Optical measurements were performed to determine density values, TVI curves, gamut volume to investigate the factors influencing tone reproduction quality. Magnified images were used to evaluate substrate-ink interaction.